MUV AKKİTZADE MEHMED PERTEY'İN DİV ANINDA ATASÖZLERİ VE DEYİMLERİN KULLANIMI - Ulucan, Mehmet (Fırat University, 2005)
Proverbs and idioms are two of the most important elements of a language. Proverbs and idioms, which are of importance in view of expressian ability and vocabulary of a language, are also veıy important in view of art and literature. They are among the language product which are mostly used among all the Turkish clans with their eliche strucıures as well as adapting to the change and developman! of the language. Muvakk.itzade Mehmed Pertev, who lived in the I gıh centuıy, isa Divan poet who used proverbs and idioms veıy often successfully in his Divan. In this study, we tried to state the use of the proverbs and idioms, that took place in Muvakk.itzade Mehmed Pertev's Divan.
Keywords: Religious Studies; Din Araştırmaları